Implementing ABS Regime in Nepal through Community Based Biodiversity Management Framework - Poudel, Bikash; Shrestha, Pitamber; Tamang, Bir Bahadur; Subedi, Abiskar (Journal of Agriculture and Environment, 2010)
It is very evident that there is lack of well accepted and verified mechanisms as well as institutional set up for the realization of farmers' rights, including the effective implementation of International Regime on Access to and Benefit Sharing (IRABS). Community Biodiversity Management (CBM) embed good practices, proven to be effective in in-situ conservation of biodiversity through conservation through use, they also provide a base for a range of practices which serve the basis for IRABS to be affable and affordable to local communities. CBM encompasses the good practices serving documentation, conservation, facilitating exchange, providing access to genetic resources and associated traditional knowledge. Moreover, CBM also provide institutional structure and mechanism to share the benefits accruing from commercial use of the genetic resources, directly and indirectly. Key words: Genetic resources; Associated traditional knowledge; Access and benefit sharing; farmers’ rights; Community biodiversity management The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 148-157 Uploaded date: 16 September, 2010